Natural regeneration of Alstonia spectabilis in small-scale privately-owned forest in Gunungkidul, Yogyakarta, Indonesia - BELGIS RAFFLESIA PUTRI WARDANI; WINASTUTI DWI ATMANTO; WIDIYATNO WIDIYATNO; NESTY PRATIWI ROMADINI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Wardani BRP, Atmanto WD, Widiyatno, Romadini NP. 2023. Natural regeneration of Alstonia spectabilisin small-scale privately-owned forest in Gunungkidul, Yogyakarta, Indonesia. Biodiversitas 24: 3723-3734. Alstonia spectabilisis a species that serves as an indicator of the dry deciduous forest type and has the potential to be utilized commercially or to support conservation programs. The development pattern, specifically in small-scale privately-owned forest (SSPF) in Gunungkidul, still relies on natural regeneration. The differences in management between agricultural (tegalan) and forested land (wana) affect the abundance and characteristics of A. spectabilis natural regeneration. Due to its great potential to be developed in the future, information on the abundance and natural regenerationin SSPF is needed. This study was conducted by creating observation plots in tegalan and wanain Sidoharjo Village, using uniform systematic sampling with a random start method and a sampling intensity of 10%. This study aimed to determine the density and diversity of tree stand as well as the distribution pattern of A. spectabilis natural regeneration. A total of 13 nested sampling plots (0.52 ha in total size) were made to observe seedlings, saplings, pole, and tree in each study area. The number and characteristics of natural regeneration were shown to be impacted by management differences between tegalan and wana. Wana had a high canopy closure of 91%, compared to 72% for tegalan. Additionally, the greater density value of 9423 ind. ha-1in wana compared to tegalan, which had 1154 ind. ha-1 at all growth levels with a random distribution pattern, showed a stronger potential for A. spectabilis for natural regeneration. The findings indicated that wana has a greater potential for seed sources with favorable environmental conditions for the survival of A. spectabilis natural regeneration.